Systematics and biogeography of Bornean geckos of the genus Cnemaspis Strauch, 1887 (Sauria: Gekkonidae), with the description of a new species - Das, Indraneil; Bauer, Aaron M. (National University of Singapore, 1998)
Three s pe cies of the gekkonid genus Cnemaspis, on e of them new, are shown to occur on Borneo. The ranges of the species appear to hug the north -wes tern coast of Borneo, all species being recorded from Sarawak State, East Malaysia. Such a distribution is similar to that reported for a lineage of the Dipterocarpaceae , with affinities in peninsular Malaya and the Rhiau Archipelago. It is thought that the present day distribution of the gekkonids may be influenced by the drainage of the ancient river basins of Sundaland which p r esumably stopped their dispersal into central and eastern Borneo